2016
DOI: 10.1039/c5ra22452g
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of pea protein for increased satiety and improved foaming properties

Abstract: Pea protein was successfully encapsulated into a lipophilic carrier through PGSS®. HPT-scCO2of pea protein has enabled higher foam stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Stone et al (2015) found that pea proteins isolates extracted by salt precipitation had better foaming properties than those obtained by alkaline extraction or micellar precipitation. High-pressure supercritical CO 2 extraction seems useful to improve the foaming properties of pea protein extracts (Saldanha Do Carmo et al, 2016), while additives (e.g. non-surface-active maltodextrin, guar gum and alginate) may considerably improve the foaming stability of pea protein isolates (Mohanan et al, 2020;Moll, Grossmann, Kutzli, & Weiss, 2019).…”
Section: Foam Formation and Stabilitymentioning
confidence: 99%
“…Stone et al (2015) found that pea proteins isolates extracted by salt precipitation had better foaming properties than those obtained by alkaline extraction or micellar precipitation. High-pressure supercritical CO 2 extraction seems useful to improve the foaming properties of pea protein extracts (Saldanha Do Carmo et al, 2016), while additives (e.g. non-surface-active maltodextrin, guar gum and alginate) may considerably improve the foaming stability of pea protein isolates (Mohanan et al, 2020;Moll, Grossmann, Kutzli, & Weiss, 2019).…”
Section: Foam Formation and Stabilitymentioning
confidence: 99%
“…The main amino acid in pea legumin α-chain is Glu, while the β-chain is rich in Val, Ala, and Leu and presence of high levels of Glu in proteins enhance protein-solvent interactions, which improves functionality ( 15 ). However, the globular nature of pea proteins hinders their flexibility as the structure is densely packed due to the presence of disulfide linkages, low surface charge density, hydrophobic effects, hydrogen bonds, electrostatic and van der Waals forces, which ultimately impairs solubility and other protein functionalities ( 16 19 ). Furthemore, the secondary structure of pea proteins is higher in the rigid β-sheet (30–41%), which contributes to the low solubility when compared to animal proteins (egg white and whey) with lots of the flexible α-helical structure ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, pea protein is mainly composed of 7S/11S globulin (salt-soluble, 65% to 80% of total) and albumin 2S (water-soluble, 10% to 20%) protein classes (Karaca, Low, & Nickerson, 2011), and contains high levels of lysine, which can be used to balance its deficiency in cereal-based diets (Iqbal, Khalil, Ateeq, & Khan, 2006). Compared to soybean protein, pea protein is generally recognized as a nonfood allergen with relatively high nutritional value and without genetic modification, offering a clean label for food products (Day, 2013;Krefting, 2017). Many studies suggested that pea protein (in many cases, pea protein hydrolysates [PPHs] and specific peptide fractions) has antioxidant (Ndiaye, Vuong, Duarte, Aluko, & Matar, 2012;Sun & Xiong, 2015), antihypertensive (Aluko et al, 2015;Liao, Fan, Liu, & Wu, 2019), anti-inflammatory (Ndiaye et al, 2012), lowering cholesterol (Sirtori et al, 2012), and modulating intestinal bacteria activities (Swiatecka, Markiewicz, & Wroblewska, 2012;Swiatecka, Narbad, Ridgway, & Kostyra, 2011).…”
Section: Introductionmentioning
confidence: 99%